PASTORAL KONSELING TERHADAP ANAK REMAJA KRISTEN YANG MENGALAMI DAMPAK BROKEN HOME - Yan Mangoli, Yefta (Sekolah Tinggi Teologi Sangkakala & Sekolah Tinggi Jemaat Kristus Indonesia, 2024)
Broken homes are not only experienced by families outside of Christianity, but in Christian families, broken homes also happen a lot. When a broken home occurs, it will have various impacts, especially for the teenage children in that family. Adolescence is a crucial period in the human body, so pastoral counseling assistance is very important for teenagers who experience broken homes. For this reason, the aim of this research is to examine the impact experienced by teenagers who experience broken homes and the importance of pastoral counseling assistance services for them. In this research, descriptive qualitative methods were used. Through studies that have been carried out both in the Bible and literature studies related to the topic of discussion. The research results show that broken home families have a very bad impact on the growth of teenage children in terms of mental, behavioral, social and spiritual aspects. Therefore, effective pastoral counseling assistance services are needed to restore this situation. Such as pastoral counseling services with Supportive-counseling, Confrontational-counseling, Educative-counseling, spiritual-counseling approaches.